Development of interactive POP ES multimedia teaching materials based on guided inquiry - Hidayah; Praherdhiono, Henry; Untari, Sri (Jurnal Bidang Pendidikan Dasar, 2025)
The primary objective was to enhance student engagement, learning outcomes, and motivation. The research was motivated by limited classroom learning time, low achievement levels, and students’ lack of enthusiasm, as well as challenges faced by parents in supporting online education. The study employed the Lee and Owens research and development (R&D) framework, which includes five main stages: needs analysis, design, development, implementation, and evaluation.For data analysis, the quantitative data (pre-test and post-test scores) were analyzed using descriptive statistics, particularly to measure the percentage of students achieving learning completeness.The findings indicated that the teaching materials achieved high validity (97% approval from subject matter and media experts), excellent practicality (97% approval from teachers and 92% from students), and strong effectiveness, with 87.5% of students achieving learning proficiency. The study concluded that the developed teaching materials are effective for classroom use, with recommendations for further customization to better align with student competencies.